2011
DOI: 10.1159/000324469
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Independent Wheat-Induced Anaphylaxis Caused by ω-5 Gliadin in Mice

Abstract: Background: ω-5 Gliadin is known as a major allergen in wheat-dependent exercise-induced anaphylaxis. The characteristics that make ω-5 gliadin an allergen remain unclear. Methods: Mice were sensitized by means of intraperitoneal injection of gliadin fractions together with the adjuvant alum. Anaphylactic responses were assessed by measuring body temperature and voluntary physical activity. Specific IgE levels in mouse serum were evaluated by ELISA. After oral administration of proteins to mice, concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(48 reference statements)
0
4
0
Order By: Relevance
“… 16 18 Tanaka et al . 19 have indirectly shown that the ω-5 gliadin is absorbed relatively well from the gastrointestinal tract compared to other gliadins by measuring the serum concentrations of the gliadins in a mouse model during exercise or rest, thus supporting the ω-5 gliadin as the major allergen that causes WDEIA. These findings suggest that the subject’s physical conditions may determine the absorption rate of gliadins, and then the enhanced serum concentration of ω-5 gliadin induces anaphylaxis in the previously sensitized subjects.…”
Section: Discussionmentioning
confidence: 95%
“… 16 18 Tanaka et al . 19 have indirectly shown that the ω-5 gliadin is absorbed relatively well from the gastrointestinal tract compared to other gliadins by measuring the serum concentrations of the gliadins in a mouse model during exercise or rest, thus supporting the ω-5 gliadin as the major allergen that causes WDEIA. These findings suggest that the subject’s physical conditions may determine the absorption rate of gliadins, and then the enhanced serum concentration of ω-5 gliadin induces anaphylaxis in the previously sensitized subjects.…”
Section: Discussionmentioning
confidence: 95%
“…During systemic anaphylaxis, decreases in whole-body temperature are commonly observed [20,21]. In this study, rectal temperature was measured 30 min after the OVA challenge to evaluate anaphylactic symptoms (Figure 1).…”
Section: Measurement Of Body Temperaturementioning
confidence: 99%
“…Gliadin was extracted from soft wheat flour (Nisshin Flour Milling Inc., Japan) as described previously [19,20]. The extracted gliadin was dialyzed against 0.1% acetic acid for 24 h and then lyophilized.…”
Section: Enzymatic Hydrolysis and Acid Deamidation Of Gliadinmentioning
confidence: 99%
“…For the evaluation of IgE-binding capacity and CD4+ T cell proliferation of degraded gliadins in vitro, the gliadin-induced wheat allergy model was used as described previously with some Li/Miyakawa/Takano/Nakajima-Adachi/ Tanokura/Hachimura Int Arch Allergy Immunol 2020;181:446-455 448 DOI: 10.1159/000506945 modifications [19]. Intraperitoneal injections of mice (6 weeks old) with 50 µg of gliadin absorbed onto alum were performed once every 10 days for four times as sensitized mice.…”
Section: Gliadin-induced Wheat Allergy Modelmentioning
confidence: 99%